ANALYSIS OF HOUSEHOLD POVERTY AT SOI VILLAGE, WEST MARAWOLA DISTRICT, SIGI REGENCY - Purwanto, Jamaludin Abdi; Rauf, Rustam Abd.; Damayanti, Lien (Tadulako University, 2018)
This research aims at finding out the level of Â household poverty and analyzing the factors influencing the household poverty. The data were analyzed by using headcount index analysis, poverty gap analysis, distribution revenue analysis, total revenue of household analysis, and regression analysis. The poverty level can be seen from the seriousness of poverty index, namely 1.72 which means the poor household expenses various with the acerage value 1.72. the distribution revenue at Soi village, west Marawola district, Sigi regency showed that the average value of household income in 2017 was 246.000, with the coefficient Gini Ratio 0.22 or in the low inequality category. The results of regression analysis showed that the coefficient of terminated (R2) was 0.472. the total of household income variable gave negative significant influence with the coefficient of elasticity -2.341 (p < 0,05), the number of elasticity 3.325 (p<0.05), the age of head of household variable gave negative variable of land ownership gave positive insignificant influence with the value 0.726 and dummy variable of educational status of household gave positive significant influence with the value 0.633.